In silico Study to Optimize the Dosage of Oleuropein with Metformin in Diabetes Management - Joshi, Darshna M.; Patel, Jignesh; Bhatt, Hardik (Iraqi Journal of Science, 2023)
Type 2 diabetes mellitus (T2DM) is a potentially fatal metabolic disorder worldwide, in this COVID-19 era. Long-term allopathic treatment has a variety of side effects, prompting the search for alternative therapies. Oleuropein, the primary bioactive ingredient of Olive Leaf Extract (OLE), has shown noteworthy actions to control T2DM. The present study provides a dynamic study of % improvement in GLUT4 concentration with different doses of metformin (150mg-500mg) in combination with 500mg using a dynamic in silico model developed in Cell Designer 4.4.2, a system biology tool. The results indicated that 300mg of metformin and 500mg of oleuropein is the optimum combination to treat diabetes, ensuring a 2% improvement in GLUT4 concentration and an effective reduction in the dose of the allopathic drug metformin when taken in combination with OLE for the improvement in T2DM. The optimal dose of metformin with oleuropein was obtained successfully using our proposed in silico dynamic model. The research could be used to create an in vivo model to examine the effectiveness of herbal medicine for T2DM.